Efeitos da liberação miofascial instrumental no desempenho físico de corredores de 400 metros : um ensaio clínico randomizado - Silveira, Rodrigo Pimentel da (2023)
Introduction: Myofascial release is one of the main manual therapy techniques used by physiotherapists to relieve pain, edema and inflammation of the myofascial tissue, aiding in its recovery. Evidence suggests that the technique can help improve physical performance in runners. We propose that instrumental myofascial release may have a restorative effect on myofascial tissue, increasing range of motion (ROM) and pressure pain threshold (PPL), contributing to improved running times. Objectives: To investigate the immediate effects of instrumental myofascial release, applied between two 400- meter runs or applied preemptively to the first run, on physical performance, ROM and PDL in runners. Methods: 30 trained subjects of both sexes were randomized into 3 groups: myofascial release (n=10) (31.7 ± 9.5 years), control (n=10) (37.2 ± 12.4 years) and preemptive (n=10) (40.5 ± 12 years). The subjects completed two 400-meter runs on an athletics track, separated by a 30-minute rest. During this period, an instrumental myofascial release protocol was carried out, using an instrument known as a boomerang, in the release group or placebo tens in the control group. In the preemptive group, instrumental myofascial release was performed before the first run. The technique was applied to the lower limbs (quadriceps, hamstrings and triceps sural) for 2 minutes in each muscle group. The times of the two runs were compared, as well as ADM (flexometer) and LDP (algometer). Results: There were no significant differences between the release, control and preemptive groups in running time (p=0.578), ROM (p=0.170/0.359 hip flexion/extension; p=0.069/0.404 dorsiflexion/plantar flexion; p=0.307 knee flexion) and LDP (p=0.747 quadriceps; p=0.242 hamstrings; p=0.267 sural triceps). Conclusion: The data from our study allow us to state that instrumental myofascial release, when applied between two 400-meter runs or preemptively to the first run, did not improve the physical performance, ROM and PDL of the runners.